2020
DOI: 10.1038/s41598-020-64326-4
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in miRNA binding sites involved in metabolic diseases in mice and humans

Abstract: Type 2 diabetes and obesity are well-studied metabolic diseases, which are based on genetic and epigenetic alterations in combination with an obesogenic lifestyle. The aim of this study was to test whether SNPs in miRNA-mRNA binding sites that potentially disrupt binding, elevate the expression of miRNA targets, which participate in the development of metabolic diseases. A computational approach was developed that integrates transcriptomics, linkage analysis, miRNA-target prediction data, and sequence informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Additionally, let-7i-5p is the only miRNA which is 100% conserved between human and mouse. Even though miR-130a-3p, miR-152-3p and let-7i-5p exhibit high level of conservation (96%, 97% and 91%, respectively), we and others previously demonstrated that a single nucleotide polymorphism can alter the binding to the target mRNA [14]. Hence, we hypothesized let-7i-5p is the most promising potential prediabetes marker.…”
Section: Identification Of Six Mirnas In Plasma Of Women With Prediab...mentioning
confidence: 85%
“…Additionally, let-7i-5p is the only miRNA which is 100% conserved between human and mouse. Even though miR-130a-3p, miR-152-3p and let-7i-5p exhibit high level of conservation (96%, 97% and 91%, respectively), we and others previously demonstrated that a single nucleotide polymorphism can alter the binding to the target mRNA [14]. Hence, we hypothesized let-7i-5p is the most promising potential prediabetes marker.…”
Section: Identification Of Six Mirnas In Plasma Of Women With Prediab...mentioning
confidence: 85%
“…Since currently available studies have implied the relationship between PPFIA4 and metabolism regulation (8)(9)(10), an important part of the present study was to evaluate if PPFIA4 upregulation was linked to glycolysis of colon cancer. Currently, a number of genes have been identified to be associated with glycolysis of cancers, such as ZBTB7A (23), HMGA1 (24) and CD36 (25).…”
Section: Discussionmentioning
confidence: 99%
“…The literature data show that miRNA sequences in murine models are comparable to those in humans [ 8 , 34 ]. This led some authors to hypothesizing a translation of the results found in mice to humans.…”
Section: Discussionmentioning
confidence: 99%